2015
DOI: 10.1371/journal.pone.0128816
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Cancer Therapy with a Novel Anti-CD37 Beta-Particle Emitting Radioimmunoconjugate for Treatment of Non-Hodgkin Lymphoma

Abstract: 177Lu-DOTA-HH1 (177Lu-HH1) is a novel anti-CD37 radioimmunoconjugate developed to treat non-Hodgkin lymphoma. Mice with subcutaneous Ramos xenografts were treated with different activities of 177Lu-HH1, 177Lu-DOTA-rituximab (177Lu-rituximab) and non-specific 177Lu-DOTA-IgG1 (177Lu-IgG1) and therapeutic effect and toxicity of the treatment were monitored. Significant tumor growth delay and increased survival of mice were observed in mice treated with 530 MBq/kg 177Lu-HH1 as compared with mice treated with simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
2
27
0
2
Order By: Relevance
“…In addition, we also evaluated the therapeutic effect of Lu-labeled rituximab led to lethal toxicity in mice (45). To avoid this, we applied therapeutic doses of 7.0 AE 1.48 MBq in case of 177 Lu-DTPA-rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also evaluated the therapeutic effect of Lu-labeled rituximab led to lethal toxicity in mice (45). To avoid this, we applied therapeutic doses of 7.0 AE 1.48 MBq in case of 177 Lu-DTPA-rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Resolution was measured by a capillary tube. A series of phantom measurements with spheric insertions (2,4,8,16, and 113 mL) was also performed. Initial activity concentration in the spheres was 0.69 MBq/mL, with subsequent activity concentrations being 0.37, 0.13, and 0.03 MBq/mL.…”
Section: Scanner Calibration and Phantom Measurementsmentioning
confidence: 99%
“…Considering that these 2 ARCs are used after patients have been treated with several rounds of rituximab, which also targets CD20, a conjugate that targets a different antigen would be desirable. 177 Lu-lilotomab satetraxetan (Betalutin [Nordic Nanovector ASA], previously referred to as 177 Lu-DOTA-HH1) is a novel ARC, in which the lilotomab antibody binds to CD37 antigens expressed on malignant B cells (4,5). 177 Lu is a b-emitter with a mean b-energy of 0.133 MeV (mean and max b-range in water, 0.25 and 1.9 mm, respectively) that also emits photons with g-energies of 113 (6%) and 208 keV (11%), permitting g-camera and SPECT/CT imaging as a means of dosimetry (6).…”
mentioning
confidence: 99%
“…Today radioimmunotherapy is mainly used in those patients experiencing relapse from chemotherapy and immunotherapy. We have previously shown that 177 Lu‐lilotomab can target and deliver radiation selectively to lymphoma tumour cells and xenografts, and the treatment is currently being tested clinically for treatment of both aggressive and indolent NHL. In this study, we showed that 177 Lu‐lilotomab can interact synergistically with rituximab to give an increased anti‐tumour effect, prolonging the survival of mice with s.c. NHL xenografts.…”
Section: Discussionmentioning
confidence: 85%
“…CD37 is an internalising transmembrane glycoprotein strongly expressed on mature B lymphocytes, including normal and neoplastic cells . 177 Lu‐lilotomab has shown strong anti‐tumour effect in preclinical models and in a completed phase 1/2a clinical trial…”
Section: Introductionmentioning
confidence: 99%